2020
DOI: 10.1177/1359105320918351
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment on young adult depression: A moderated mediation model of negative automatic thoughts and self-compassion

Abstract: This study examines the mediating role of negative automatic thoughts on the link between childhood maltreatment and young adult depression, and the moderating role of self-compassion in this indirect link. College students ( N = 578) completed self-report questionnaires assessing the mentioned study variables. The results showed that childhood maltreatment was positively associated with young adult depression via negative automatic thoughts. Moreover, self-compassion moderated this indirect link such that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
3
28
0
Order By: Relevance
“…Our study found that bullying victimization further increased LBC’s depression through negative thoughts. The cognitive model of depression theorized that negative experiences, such as bullying victimization, might foster negative reviews (as a form of cognitive vulnerability) due to a person’s information processing biases that lead to the appearance of depressive symptoms ( Hou et al, 2020 ). When LBC are bullied, their normal cognitive system will collapse, and they cannot think rationally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that bullying victimization further increased LBC’s depression through negative thoughts. The cognitive model of depression theorized that negative experiences, such as bullying victimization, might foster negative reviews (as a form of cognitive vulnerability) due to a person’s information processing biases that lead to the appearance of depressive symptoms ( Hou et al, 2020 ). When LBC are bullied, their normal cognitive system will collapse, and they cannot think rationally.…”
Section: Discussionmentioning
confidence: 99%
“…Self-compassion is a very positive self-regulation strategy that helps reduce negative emotions, such as depression by acknowledging discomfort and self-kindness, contributing to healthy mental development ( Neff, 2003 ). Previous studies have shown that negative thoughts and self-compassion are important factors that may mediate the association between adverse experiences and depressive symptoms ( Wu et al, 2018 ; Hou et al, 2020 ). Therefore, this study will simultaneously explore the mediating role of negative thoughts and self-compassion in the relationship between bullying victimization and depression in LBC.…”
Section: Introductionmentioning
confidence: 99%
“…Three studies originated from the US (Boykin et al, 2018;Miron et al, 2016;Reffi et al, 2019), two from Canada (Tanaka et al, 2011;Vettese et al, 2011), one from China (Hou et al, 2020), and one from Spain (Játiva & Cerezo, 2014). Among the included studies, all of them were peer-reviewed primary articles with six cross-sectional studies (Boykin et al, 2018;Hou et al, 2020;Játiva & Cerezo, 2014;Miron et al, 2016;Reffi et al, 2019) and one cohort study (Tanaka et al, 2011). There were three out of seven included studies that used solely female samples (Boykin et al, 2018;Miron et al, 2016;Reffi et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…However, two of those three studies used female college students enrolled in psychology courses at a large Midwestern university (Miron et al, 2016;Reffi et al, 2019), while the third used female college students non-selectively (Boykin et al, 2018). Two out of seven included studies had similar male to female participant proportions (Hou et al, 2020;Tanaka et al, 2011), and two of the included studies had a much higher proportion of male than female participants (71.6% to 28.4% and 65.4% to 34.6%, respectively; Játiva & Cerezo, 2014;Vettese et al, 2011). While all included studies enrolled youth participants, three in particular recruited participants over 18 years old (Boykin et al, 2018;Miron et al, 2016;Reffi et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As one of the most common psychiatric disorders, the relationship between depression and ACE has been the focus of recent research. Partial studies explored the impact of ACE on adult depression from a single dimension, such as childhood maltreatment (Hou et al, 2020) and early parental loss (Høeg et al, 2017). However, multiple ACE often occurred simultaneously (Edwards et al, 2003; Finkelhor et al, 2007), and analyses of single ACE may overestimate their impact.…”
Section: Introductionmentioning
confidence: 99%